2021
DOI: 10.1021/acs.jafc.0c06338
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into a Novel Esterase from the East Pacific Rise and Its Improved Thermostability by a Semirational Design

Abstract: Lipolytic enzymes are essential biocatalysts in food processing as well as pharmaceutical and pesticide industries, catalyzing the cleavage of ester bonds in a variety of acyl chain substrates. Here, we report the crystal structure of an esterase from the deep-sea hydrothermal vent of the East Pacific Rise (EprEst). The X-ray structure of EprEst in complex with the ligand, acetate, has been determined at 2.03 Å resolution. The structure reveals a unique spatial arrangement and orientation of the helix cap doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 49 publications
1
12
0
Order By: Relevance
“…5 In addition, the low thermal stability of L-ASNase hinders acrylamide mitigation efficiency in thermally processed food, 6,7 which also increases the risk of microbial contamination and overall production costs. 8 Thus, L-ASNases with desirable thermostability for addressing these shortcomings have always been pursued for the clinical and food industries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 In addition, the low thermal stability of L-ASNase hinders acrylamide mitigation efficiency in thermally processed food, 6,7 which also increases the risk of microbial contamination and overall production costs. 8 Thus, L-ASNases with desirable thermostability for addressing these shortcomings have always been pursued for the clinical and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the short half-life, commercial l -ASNase coming from Escherichia coli (EcA) and Erwinia chrysanthemi (ErA) have a high-dose-dependent disadvantage for ALL treatment, causing severe toxic effects on patients . In addition, the low thermal stability of l -ASNase hinders acrylamide mitigation efficiency in thermally processed food, , which also increases the risk of microbial contamination and overall production costs . Thus, l -ASNases with desirable thermostability for addressing these shortcomings have always been pursued for the clinical and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilizing mutations reduce active-site flexibility, which is required for optimal catalysis. Consequently, increased stability of the mutants usually comes at the expense of catalytic activity. , Although the trade-off problem of stability and activity has been overcome in many thermostable mutants, substantial exploration is required to unlock the intrinsic mechanism of balancing stability and activity. , Future attempts can be made to rationally modify the catalytic pocket of mutant M4 to restore the enzyme’s lost activity, attaining a balance between stability and activity. The interaction among subunits significantly contributed to thermostability improvement, which would not be easily affected by the modification of internal catalytic pockets.…”
Section: Discussionmentioning
confidence: 99%
“…Proline possesses only one rotatable angle and cannot form the H-bond . It has been suggested that pro-capping the N-terminals of the α-helix/β-sheet can increase the enzyme’s thermostability. …”
Section: Discussionmentioning
confidence: 99%
“…The strategy of rigidifying flexible sites has also been applied to many other enzymes including chondroitinase ABC (Kheirollahi et al, 2017), esterase (Zhu et al, 2021), artificial metalloenzymes (Obrecht et al, 2021) and so forth.…”
Section: Stabilitymentioning
confidence: 99%